2019
DOI: 10.1038/s41537-019-0083-y
|View full text |Cite
|
Sign up to set email alerts
|

A technology-assisted life of recovery from psychosis

Abstract: Developments in digital health technologies have the potential to expedite and strengthen the path towards recovery for people with psychosis. This perspective piece provides a snapshot of how a range of digital technologies can be deployed to support a young adult’s efforts to cope with schizophrenia-spectrum illness. In conjunction with a day in the life of this individual, we provide examples of innovations in digital health research designed for this clinical population, as well as brief summaries of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Text messaging using mobile phones appears to be supportive in patient recovery, even in severe mental illness involving psychosis. 81 It has been shown that telehealth is equivalent to in-person care in respect of accuracy of diagnosis, effectiveness of therapy, quality of care and satisfaction of patients . 82 For example, telehealth problem solving therapy was shown to be as efficacious as face-to-face therapy in depressed low-income homebound elderly adults.…”
Section: Digital Technologies In Mental Health Carementioning
confidence: 99%
“…Text messaging using mobile phones appears to be supportive in patient recovery, even in severe mental illness involving psychosis. 81 It has been shown that telehealth is equivalent to in-person care in respect of accuracy of diagnosis, effectiveness of therapy, quality of care and satisfaction of patients . 82 For example, telehealth problem solving therapy was shown to be as efficacious as face-to-face therapy in depressed low-income homebound elderly adults.…”
Section: Digital Technologies In Mental Health Carementioning
confidence: 99%
“…Thus, the field's next steps will also be critical in ensuring digital health is used today to deliver the best care during the current crisis, ready for any resulting mental health spike following the immediate crisis, and prepared to support future crises as well as care as usual. In this perspective piece, we draw largely from our team's experience with digital health and recognize the impressive global innovation and research in this space that cannot be captured in any single piece [2][3][4][5][6][7][8][9].…”
mentioning
confidence: 99%
“…1) does not do justice to the many excellent apps not mentioned and the teams behind each one mentioned. FOCUS (Ben-Zeev et al, 2019) from Dr. Dror Ben-Zeev, and PRIME (Schlosser et al, 2018) from Dr. Danielle Schlosser, Intellicare from Dr. David Mohr (Mohr et al, 2017), and CBT2Go (Depp et al, 2019) from Dr. Colin Depp as just some examples of mobile health tools for SMI. Using digital phenotyping and smartphone surveys/sensors to better monitor patients' real time, longitudinal, and dynamic experience of mental health is feasible with apps like mindLAMP from our group , Cross Check from Dr. John Kane (Ben-Zeev et al, 2017) and many others like the MONARCHA by Dr. Jakob Bardram plus many more (Bardram and Mati, 2020) These smartphone digital data streams can be used predict relapse (Barnett et al, 2018), and create personalized care plans responsive to the psychological and social environments of patients.…”
mentioning
confidence: 99%